Teaching nutrition in schools: Do our students practice what we teach? - Peters, J. (1980)
Three problems faced by nutrition educators are: 1) the irrelevance of what is taught in school to the lives some students eventually lead; 2) reaching the community beyond the classroom; and 3) the competitive, often inaccurate education provided by the mass media. One suggestion for overcoming these problems is to put more emphasis on the Who and How and less on the What. Strategies for using the media effectively are also discussed
Keywords: Nutrition education